Post-operative Atrial Fibrillation Impacts on Outcomes in Transcatheter and Surgical Aortic Valve Replacement - Jeong, Hyung Ki; Yoon, Namsik; Kim, Ju Han; Lee, Nuri; Hyun, Dae Yong; Kim, Min Chul; Lee, Ki Hong; Jeong, Yo Cheon; Jeong, In Seok; Yoon, Hyun Ju; Kim, Kye Hun; Park, Hyung Wook; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Atrial fibrillation (AF) in severe aortic stenosis (AS) has poor outcomes after transcatheter and surgical aortic valve replacement (TAVR and SAVR, respectively). We compared the incidence of AF after aortic valve replacement (AVR) according to the treatment method and the impact of AF on outcomes. Methods: We investigated the incidence of AF and clinical outcomes of AVR according to whether AF occurred after TAVR and SAVR after propensity score (PS)-matching for 1-year follow-up. Clinical outcomes were defined as death, stroke, and admission due to heart failure. The composite outcome comprised death, stroke, and admission due to heart failure. Results: A total of 221 patients with severe AS were enrolled consecutively, 100 of whom underwent TAVR and 121 underwent SAVR. The incidence of newly detected AF was significantly higher in the SAVR group before PS-matching (6.0% vs. 40.5%, P < 0.001) and after PS-matching (7.5% vs. 35.6%, P = 0.001). TAVR and SAVR showed no significant differences in outcomes except in terms of stroke. In the TAVR group, AF history did not affect the outcomes; however, in the SAVR group, AF history affected death (log rank P = 0.038). Post-AVR AF had a worse impact on admission due to heart failure (log rank P = 0.049) and composite outcomes in the SAVR group. Post-AVR AF had a worse impact on admission due to heart failure (log rank P = 0.008) and composite outcome in the TAVR group. Conclusion: Post-AVR AF could be considered as a predictor of the outcomes of AVR. TAVR might be a favorable treatment option for patients with severe symptomatic AS who are at high-risk for AF development or who have a history of AF because the occurrence of AF was more frequent in the SAVR group.